Analisis Dampak dan Risiko Pemindahan Ibu Kota Negara terhadap Stabilitas Inflasi di Indonesia - Farid Maulana; Maziyah Farhah; Elmesie Berlentie; Rasidah Novita Sari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The development of the National Capital City (IKN) triggers an increase in demand for goods and services, especially in the construction and basic needs sectors, which can cause a spike in regional and national inflation. Monetary policy faces new challenges, including increasing interest rates and the risk of rupiah exchange rate volatility due to dependence on foreign debt financing. These projects also influence economic distribution, creating investment opportunities, but potentially increasing economic inequality. This research emphasizes the importance of coordination between monetary and fiscal policies to mitigate negative impacts on national economic stability.